Penerapan Model Pembelajaran DMR (Diskursus Multi Representasi) untuk Meningkatkan Hasil Belajar Siswa Kelas VIII di MTs Al Kawtsar - Panti – Jember - Kurniawan, Andrik; Nurjanah, Umi; Hakim, Miftahul (JURNAL BIOSHELL, 2024)
Research on the application of the DMR Learning Model which is a model for student learning activities. The goal is to improve the learning outcomes of class VIII students at MTs Al Kawtsar Panti - Jember with 19 students being studied as respondents. The method used in this research is Classroom Action Research. This data analysis uses qualitative data analysis. Based on the results of the study, it was obtained that the learning outcomes that were initially applied to the learning model were obtained by students with 36% classical completeness. With the implementation of the DMR learning model at the stage of cycle 1, student learning outcomes have increased by reaching an average of 80.00 with a classical completeness of 57%. The implementation of one cycle of student learning outcomes has increased but has not yet reached the researcher's target. In the second cycle of research, student learning outcomes have increased with an average score of 88.42 with a classical completeness of 78%. From the results of the amount of data that has been calculated based on the criteria for the level of success, it can be categorized as GOOD. Thus, it is concluded that the application of the DMR learning model can improve student learning outcomes in class VIII MTs Al Kawtsar Panti – Jember